Social Capital and Educational Attainment Among Rural Community in Malaysia - Roslan Abdul Hakim; Russayani Ismail; Nor Azam Abdul Razak (International Journal of Management Studies, 2012)
The determinants of educational attainment among children have become one of the main research agenda among scholars, educationists and economists alike. In most studies, the focus is on the relationship between educational attainment and factors such as the quality of teachers, schools, educational technologies, curriculum design, the fi nancial and human capital aspect of the families and the ability of children themselves. Recently, the focus has been expanded to explore the relationship between social capital and educational attainment. As an addition to the existing literature, this paper attempts to investigate the impact of social capital on educational attainment using a regression analysis based on a sample of 2500 households, gathered from a rural community in Terengganu, Malaysia. Six domains of social capital are used to arrive at the index of social capital. The argument advanced in this paper is that social capital, which could be viewed as the outcome of networking, cooperation and trust at the household level, is expected to have a positive impact on a child’s educational attainment. Towards this end, we regress children’s education attainment on social capital along with other relevant independent variables, i.e. family, children, school and neighbourhood characteristics. Interestingly, the result of our study reveals that the level of social capital that a family has, is found to be signifi cant and has the expected positive sign. This finding implies that social capital at the household level appear to be a critical factor in determining a child’s educational attainment. Thus, our finding lends support to the idea that social capital is a good predictor of children’s is educational attainment.